PENGARUH CSR DAN LEVERAGE TERHADAP NILAI PERSUSAHAAN PADA PERUSAHAAN SUB SEKTOR KOSMETIK DAN KEPERLUAN RUMAH TANGGA - Juan Situmorang; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
The purpose of this research is to know the Corporate Social Responsibility and Leverage on the value of the company in the Indonesian Stock Exchange index in 2015-2019. The method on this study is purposive sampling. This study was conducted on the company's Sub-sector cosmetics and household use listed on the Indonesia Stock Exchange in 2015-2019 with the number of samples 4 companies that have been arranged by the authors. The results showed that Corporate Social Responsibility and Leverage influenced the company's value simultaneously. The CSR and leverage are not significantly significant in the value of the company registered in the Indonesian Stock exchange in 2015-2019